3D beam shape estimation based on distributed coaxial cable interferometric sensor. (7th February 2017) - Cheng, Baokai; Zhu, Wenge; Liu, Jie; Yuan, Lei; Xiao, Hai
Abstract: We present a coaxial cable interferometer based distributed sensing system for 3D beam shape estimation. By making a series of reflectors on a coaxial cable, multiple Fabry–Perot cavities are created on it. Two cables are mounted on the beam at proper locations, and a vector network analyzer (VNA) is connected to them to obtain the complex reflection signal, which is used to calculate the strain distribution of the beam in horizontal and vertical planes. With 6 GHz swept bandwidth on the VNA, the spatial resolution for distributed strain measurement is 0.1 m, and the sensitivity is 3.768 MHz m ε −1 at the interferogram dip near 3.3 GHz. Using displacement-strain transformation, the shape of the beam is reconstructed. With only two modified cables and a VNA, this system is easy to implement and manage. Comparing to optical fiber based sensor systems, the coaxial cable sensors have the advantage of large strain and robustness, making this system suitable for structure health monitoring applications.